“A Mask Looking Towards the City and the Valley”: Observations on the “Charonion” in Antioch - Kisbali, Tamás P. (Actual Problems of Theory and History of Art, 2024)
This paper presents several observations regarding a rock-cut relief situated on the mountain above Antioch on the Orontes. Due to its correspondence to a passage in John Malalas’ “Chronographia”, the monument came to be known as the “Charonion”, dated to the reign of Antiochos IV Epiphanes; however, the historicity of this evidence is disputed in scholarly literature. The relief is examined in its setting in the landscape and urban context of Antioch. It is hypothesized that it embodied the idea of divinity in unity with the city, the mountain and the river (thus also referencing the iconography of Tyche). The central figure is understood as an important local goddess. It is proposed, that a particular format — the sculptural bust — was chosen for three reasons. First, to provide a specific iconographic reference point to images of the Dea Syria. Second, to increase the relative monumentality of the relief, while retaining a sense of openness and approachability of the depicted goddess. Third, to display the connection of the image with the mountain. The rock-cut monument is compared to Syrian funerary and votive sculpture of the first centuries of the 1st millennium A.D., where strict hierarchical compositions (e. g. the positioning of a smaller secondary figure next to a main central one) are found often. This also means, that the date of the creation of the relief can be later than the 2nd century B.C. Finally, regarding the “Charonion”, in this paper it is proposed that at some point in history, prior to the 6th century A.D., there had been a sacred cave nearby, perhaps related to the relief, and by Malalas’ time the term shifted to denote the whole area, including the rock-cut monument.
Keywords: Antioch on the Orontes; ancient Syria; rock-cut monuments; John Malalas; Charonion